2018
DOI: 10.1007/s00586-018-5603-3
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a diffuse type tenosynovial giant cell tumor in the thoracic spine mimicking spinal metastasis by frozen recapping laminoplasty in a patient with thyroid cancer

Abstract: TGCT-D can mimic metastasis in PET/CT and should be included in the differential diagnosis if a lytic lesion affecting the posterior elements of the vertebrae involves the facet joints. CT-guided biopsy is recommended for accurate diagnosis when an occult tumor, such as TGCT, is incidentally detected on PET-CT, even in patients with a history of malignant neoplasm. Frozen recapping laminoplasty is useful for complete resection of a spinal tumor, preventing local recurrence, and preservation of the posterior sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…18 F-FDG PET/CT imaging of spinal GCTTS has been infrequently reported [11][12][13][14]. In previous studies, GCTTS showed a high 18 F-FDG uptake [11][12][13][14]. All the lesions in our study showed high 18 F-FDG uptake, consistent with previous report findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…18 F-FDG PET/CT imaging of spinal GCTTS has been infrequently reported [11][12][13][14]. In previous studies, GCTTS showed a high 18 F-FDG uptake [11][12][13][14]. All the lesions in our study showed high 18 F-FDG uptake, consistent with previous report findings.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, GCTTSs showed moderate to marked enhancement, probably due to the proliferative capillaries within the collagenous stroma within the lesion [10]. 18 F-FDG PET/CT imaging of spinal GCTTS has been infrequently reported [11][12][13][14]. In previous studies, GCTTS showed a high 18 F-FDG uptake [11][12][13][14].…”
Section: Discussionsupporting
confidence: 57%